2019
DOI: 10.1016/j.freeradbiomed.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Differential peroxiredoxin hyperoxidation regulates MAP kinase signaling in human articular chondrocytes

Abstract: The peroxiredoxin (Prx) family of Cys-dependent peroxidases control intracellular levels of H 2 O 2 and can regulate signal transduction. Inhibition of the Prxs, through hyperoxidation amongst other mechanisms, leads to oxidative stress conditions that can alter homeostatic signaling. To determine the effects oxidation of Prx1-Prx3 has on MAP kinase and IGF-1 signaling events in human chondrocytes, this study used 2-methyl-1,4-naphthoquinone (menadione) and 2,3-dimethyl-1,4naphthoquinone (DMNQ) as H 2 O 2 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 42 publications
3
15
0
3
Order By: Relevance
“…Mitochondrial dysfunction within the menisci after spaceflight is also in agreement with altered mitochondrial dysfunction and stress observed during and after spaceflight from multiple rodent tissues and astronauts 24 These molecular and phenotypic responses in the menisci are similar in nature to the response observed in the knee and hip articular cartilage from female mice after 30 days of HLU 16 . Similar catabolic mechanisms and responses have also been observed in other in vitro and in vivo osteoarthritic models, with increased oxidative stress, reduced anabolic pathways, and evidence of mitochondrial dysfunction 42 47 . Clinically, circulating MMP levels that are also associated with collagen degradation with arthritis (e.g., MMP-3) were increased during a 21 day head-down tilt bedrest study as a spaceflight microgravity analogue 48 .…”
Section: Discussionsupporting
confidence: 71%
“…Mitochondrial dysfunction within the menisci after spaceflight is also in agreement with altered mitochondrial dysfunction and stress observed during and after spaceflight from multiple rodent tissues and astronauts 24 These molecular and phenotypic responses in the menisci are similar in nature to the response observed in the knee and hip articular cartilage from female mice after 30 days of HLU 16 . Similar catabolic mechanisms and responses have also been observed in other in vitro and in vivo osteoarthritic models, with increased oxidative stress, reduced anabolic pathways, and evidence of mitochondrial dysfunction 42 47 . Clinically, circulating MMP levels that are also associated with collagen degradation with arthritis (e.g., MMP-3) were increased during a 21 day head-down tilt bedrest study as a spaceflight microgravity analogue 48 .…”
Section: Discussionsupporting
confidence: 71%
“…The overexpression of catalase targeted to the mitochondria counteracted excessive mitochondrial H 2 O 2 , inhibited p38 activation, and promoted Akt activity and chondrocyte survival in vitro, whereas transgenic mice overexpressing catalase in the mitochondria (mitochondrial catalase [MCAT] mice) developed less severe age‐related OA ( 6 ). Likewise, adenoviral overexpression of mitochondrial Prx3 in chondrocytes was able to inhibit p38 activation and restore Akt signaling under conditions of excessive mitochondrial ROS ( 7 ). These results suggested that inhibition of excessive mitochondrial ROS may be a useful strategy to combat cartilage degradation in OA.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of 2-Cys PRDX activity without oxidative stress caused a decrease in oxPTMs in all detected sperm proteins, which suggests that, under physiological conditions, 2-Cys PRDXs are involved in redox signaling through the use of reversible oxidative modifications of a specific group of redox-sensitive proteins ( Figure 8 B). Such direct redox interactions between 2-Cys PRDXs and redox-sensitive target proteins occur in several signaling pathways, such as apoptosis signaling [ 27 , 28 ], cytokine-induced STAT3 signaling [ 9 ], platelet-derived growth factor signaling [ 29 ], MAP kinase signaling [ 30 ], and replisome activity regulation [ 31 ] of somatic cells. In sperm, the role of 2-Cys PRDXs in homeostatic signaling is poorly understood.…”
Section: Discussionmentioning
confidence: 99%